Plant growth regulators in onion-A review (Indian Journal of Arid Horticulture, 2016)
Indian horticulture becomes more mechanized and science increases the possibilities for using inputs to enhance production. The discovery of plant growth substances has proved revolutionary in increasing the production of different vegetable crops. In recent years, their use becomes more vital as they provide an immediate impact on crops and are less time consuming. There is a great potentiality of various plant growth substances in different concentration for improving  vegetative growth, yield and quality of onion. Further, theses can also be used to prevent sprouting and rotting of bulbs in storage. This paper reviews the research work done on use of various plant growth substances like auxins, gibberellins, cytokinin, ethylene, growth inhibitors and growth retardants in onion production.
Keywords: Onion; Plant growth regulators; Growth; Yield; Quality; Bolting; Shelf-life